PENGEMBANGAN APLIKASI QUIVERVISION BERBASIS PENDEKATAN INTERDISIPLINER ART AND SCIENCE PADA MATA PELAJARAN IPAS KELAS III DI SDN 064983 MEDAN HELVETIA - Aqila, Melisa; Simanihuruk, Lidia; Irsan; Mailani, Elvi; Manurung, Imelda Free Unita (STKIP Subang, 2026)
This study aims to develop a learning media in the form of the QuiverVision application based on an interdisciplinary art and science approach in the IPAS subject for third-grade students at SDN 064983 Medan Helvetia and to determine the feasibility, practicality, and effectiveness of the developed learning media. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, questionnaires, and tests. The results showed that the developed learning media was categorized as highly feasible based on expert validation, with a material expert score of 92% and a media expert score of 93.3%. In terms of practicality, the evaluation from the educational practitioner (third-grade teacher) obtained a score of 93%, while student responses reached 96.42%, indicating that the media is highly practical for use in the learning process. Furthermore, in terms of effectiveness, the results of the pretest and posttest analysis showed an average N-gain score of 0.841 with a percentage of 84.07%, which falls into the effective category. Therefore, the Quivervision-based learning media with an interdisciplinary art and science approach is considered highly feasible, highly practical, and effective as an alternative learning media for IPAS in elementary schools.